TEKNIK PEMERIKSAAN RADIOGRAFI OS FEMUR PADA KASUS FRAKTUR DI INSTALASI RADIOLOGI RSU MITRA SEJATI - TJUANDA, YUSRIWAN (LP2MTBM MAKARIOZ, 2023)
Radiographic Examination Technique of Os Femur in Fracture Cases at Radiology Hospital of RSU Mitra Sejati, aims to determine the technique of radiographic examination of Os Femur in cases of fracture in Radiology Installation of RSU Mitra Sejati and to determine the advantages and disadvantages of radiographic technique of Os Femur in fracture cases in Radiology Installation of RSU Mitra Sejati True. This type of examination uses qualitative research with a case study approach which was carried out at RSU Mitra Sejati in June 2018. The population of this study was all patients who underwent radiographic examination of the Femur Os in fracture cases at the Radiology Installation of RSU Mitra Sejati with the research sample including one person. The patient and those serving as respondents included two radiographers. This research data was taken by observing and documenting. The results of this research are that good cooperation between the radiographer and the patient is very necessary for a smooth examination. Os Femur radiography techniques with suspected fractures use AP (Antero-Posterior) and lateral projections, paying attention to patient comfort to support good image results and optimal sharpness and detail, the processing used is CR (Computed Radiography)